Serum gastrin concentration affects the self replication rate of the enterochromaffin like cells in the rat stomach. Issue 3 (March 1990) - Tielemans, Y; Axelson, J; Sundler, F; Willems, G; Håkanson, R
Abstract : The influence of antrectomy and antrum exclusion on the enterochromaffin like cell kinetics in the gastric mucosa of the rat was studied using a combination of histamine immunocytochemistry and autoradiography after in vivo labelling with tritiated thymidine. In all experimental groups, the enterochromaffin like cells were found to incorporate the DNA precursor, thus indicating an ability to divide. The serum gastrin concentration was raised by antrum exclusion and reduced by antrectomy. After antrum exclusion, the enterochromaffin like cell proliferation rate increased as indicated by a doubling of the labelling index and by the resulting enterochromaffin like cell hyperplasia (after six weeks). After antrectomy, the enterochromaffin like cell labelling index decreased to reach 25% of the control value; at this time the enterochromaffin like cell density had not decreased significantly. The observed correlation between the enterochromaffin like cell labelling indices and the serum gastrin concentration supports the hypothesis that enterochromaffin like cell proliferation is influenced by serum gastrin.